Scientific-technical outsourcing as the management tool of the ecologically focused development of the chemical enterprises. - E. A. Demcheva; V. B. Lukmanov; S. A. Panova; O. V. Makarov (Тонкие химические технологии)
Outsourcer search stages are defined. The model of the outsourcer selection is offered, allowing the enterprise to maximize the net present value as a result of research and developmental works using scientific-technical outsourcing, including solutions on environmental oriented problems